Assessment of knowledge and awareness regarding urinary tract infections among the university students of Bangladesh - Tabassum, Fatema; V, Most. Nazma; Manik, Md. Imran Nur (International Journal Of Community Medicine And Public Health, 2021)
Background: Urinary tract infections (UTIs) are the major health problems in young population. The aim of the study is to determine the knowledge and awareness about UTI among the university students of Bangladesh. Methods: The survey carried out among 403 students of different private universities of department of Pharmacy. Data were collected using structured questionnaires containing 6 questions related to the students’ demographics and 10 questions related to the knowledge and 6 questions related awareness to UTI. Data was analyzed by the Microsoft Excel version 10. Results: Among the respondents there were 61.04% female, majority of them were unmarried (93.80%) and the average limit for age was found to be 21 years. The result showed that 76.92% of respondents correctly identified bacteria as the principle pathogens forming UTIs and 80.15% suggested antibacterial drugs for the treatment of UTIs. 60.04% showed poor knowledge on the further consequences of untreated UTIs in the long run and 51.86% don’t know the adverse effect of urinary retention. This study showed that cumulatively 77.79% respondents had positive attitude towards the measures against UTIs. Among the subjects 71.46% are against holding urine , 93.80% thinks drinking plenty of water is good for heath, 94.79% wanted to contact the doctor when get ill. Conclusions: Short-term morbidity in terms of fever, dysuria, and lower abdominal pain (LAP) and may result in permanent scarring of the kidney may caused by UTIs. Students must be made aware of these symptoms and their causes and also aware about the prevention of UTIs to decrease the morbidity rate.